STRATEGI PROMOSI DALAM MENINGKATKAN KUNJUNGAN WISATA DI KABUPATEN PANDEGLANG - Kuraisin, Icin; Suhandi, Suhandi (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2024)
The purpose of this research is to examine the promotional strategies implemented by the Pandeglang Regency Tourism Office in order to increase tourist visits in Pandeglang Regency. Research methods Data collection was carried out by interviews, direct observation and documentation. Data analysis was carried out through data collection, data reduction, data presentation and drawing conclusions..The results of this research show 1. Promotion through print media such as brochures, pamphlets and electronic media as a means of promotion does not have a significant impact in increasing tourist visits because of the current tendency of society to access the internet more than conventional media, 2. Tourism events carried out by the Department of Tourism and Creative Economy of Pandeglang Regency, Banten are the most effective promotions in increasing tourist visits because every event held has a target of bringing in large numbers of visitors. Apart from that, tour agents and freelance bloggers play an active role in promoting tourism via the internet and social media